Using DEA method for determining tourism efficiency of Serbia and the surrounding countries - Ilić, Ivana; Petrevska, Ivana (Hotel and Tourism Management, 2018)
Data Envelopment Analysis (DEA method) was used for determining tourism efficiency of Serbia and the surrounding countries. Analysis is done on the basis of input and output parameters which provide objective analysis and identify the best practice. Tourism expenses and the number of beds are used as inputs, while the number of arrivals, the number of nights spent and tourism revenue in 2016 are used as output parameters. The applied analysis has shown that in the aspect of tourism 6 countries are relatively efficient, while other 9 are relatively inefficient. The efficient countries are: Montenegro, Bosnia and Herzegovina, Croatia, Greece, Austria and Albania, while Serbia, FYR Macedonia, Slovenia, Romania, Bulgaria, Italy, Hungary, Slovakia and the Czech Republic have efficiency value of: 64.49%, 54.57%, 97.82%, 86.96%, 86.38%, 83.78%, 86.38%, 69.54%, and 73.27%, respectively. In order to improve their efficiency, the inefficient countries should reduce tourism costs and the number of beds and increase some of the output parameters. This paper should give the instructions to inefficient countries how to improve their efficiency.